The Effect of Innovation, Business Adaptability, and Financial Literacy on Sustainability with Empowerment as a Moderating Variable - Permana, Muhammad Alwi; Yunizar, Yunizar; Sutisna, Sutisna (LifeSciFi, 2026)
The sustainability of food and beverage Micro, Small, and Medium Enterprises (MSMEs) is challenged by rapid market changes, digital transformation, intense competition, and limited innovation, adaptability, and financial management capacity. This study aims to examine the effect of product innovation, business adaptability, and financial literacy on the sustainability of food and beverage MSMEs, with MSME empowerment as a moderating variable. The research adopts a quantitative explanatory approach using a survey method. Data were collected through structured questionnaires distributed to food and beverage MSME owners in Bandung Regency and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that business adaptability has a significant and strong positive effect on MSME sustainability, while product innovation and financial literacy do not have a significant direct effect. MSME empowerment has a significant direct effect on sustainability and selectively moderates the relationship between business adaptability and sustainability, but does not moderate the effects of product innovation and financial literacy. These findings indicate that MSME sustainability is primarily driven by adaptive capabilities, which are strengthened through effective empowerment programs. The study highlights the importance of integrating adaptability and empowerment strategies to support sustainable MSME development.